RELEVANSI NILAI-NILAI PANCASILA DALAM SEJARAH BANGSA INDONESIA SEBAGAI BENTENG PERSATUAN INDONESIA: STUDI KASUS POLEMIK PENUTUPAN WARUNG DAGING BABI DI KOTA MEDAN 2026 - Ananda Almi Fadilah; Erika Afrilia Saputri; Intan Rezkinah; Muhammad Fahrezi; Ramlan Anri Sianturi (JURNAL ILMIAH NUSANTARA, 2026)
Indonesia's progress as a nation with diverse ethnicities, religions, cultures, and languages demonstrates that the country's population possesses a very high level of diversity. Indonesia's social structure, comprised of various ethnic groups, requires Pancasila as its fundamental national law and moral principles to maintain peaceful social interactions. This study aims to examine how Pancasila values function as a unifying force throughout Indonesian history while assessing the ban on pork sales operations in Medan City in February 2026 through an analysis of Pancasila values. This study uses a qualitative research design that utilizes the desk observation method to investigate information from various sources, including books and scientific journal articles, as well as relevant media reports that support the research subject. The research findings indicate that Pancasila values, which include tolerance and human dignity, as well as national unity, collective decision-making, and social justice, serve as important components for maintaining social harmony among diverse communities. Community disputes in Medan City indicate that the implementation of Pancasila social values faces difficulties due to difficulties in understanding government policies and the diverse needs of the community. The Indonesian government and citizens need to strengthen their understanding and practice the values of Pancasila because this will help the nation maintain its unity amidst ongoing social changes.